THE PITFALLS OF A NATION PROJECT IN OS ANÕES E OS MENDIGOS, BY MANUEL DOS SANTOS LIMA (Editora Impacto Científico, 2025)
The text aims to discuss the construction of utopias in Angolan literature in the 1960s, in the presence of Manuel dos Santos Lima as a writer engaged in the Movement for the Liberation of Angola (MPLA), alongside names such as Agostinho Neto, and the dystopia present in Os anões e os mendigos (2004), which questions the direction of post-independence, insofar as Angola's serious social problems were not resolved with the struggle for liberation. In order to understand this trajectory - from dream to disappointment - we used the theorists Pires Laranjeira, Morus, Max Weber, Salvato Trigo and others to help us trace this path of dystopia, which in order to be evaluated also relies on the help of the African literary text, an instrument of its own written history.